CASE STUDY MENGATASI STRES KERJA PERAWAT DENGAN TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) PADA PERAWAT DI RUANG CENDANA I RUMAH SAKIT BHAYANGKARA TK.I RADEN SAID SUKANTO - Lilis Dwi Septiani (2022)
Nurse work stress is one that nurses feel at work. This problem needs to be addressed because the high work stress of nurses interferes with the work productivity of nurses and will have an impact on the quality of nursing services. The results of observations made by the author in Cendana Room I Bhayangkara Tk.I Hospital Raden Said Sukanto showed that from 13 nurses on duty there were 7 nurses (54%) who had mild stress, 3 nurses who had strong stress (23%) and 3 nurses. nurses (23%) who fall into the category of normal stress. Based on these results, the authors applied evidence based nursing in the form of spiritual emotional freedom technique (SEFT) therapy on 3 nurses who had strong stress. SEFT therapy was administered for 3 consecutive days with a duration of 20 minutes per session. The posttest results after applying self-healing therapy using the expressive writing therapy method showed that there were 1 nurse (33%) who was still in the category of strong stress and 2 nurses (64%) were included in the category of mild stress. This shows that the application of evidence based nursing in the form of SEFT therapy is proven to be able to overcome work stress on nurses. It is recommended that nurses can carry out this therapy when nurses experience work stress.